The Therapeutic Communication Phenomenon of Selempang Mera Aba Idi Community in the Process of Healing People with Mental Disorders after Confinement in Stocks - Sri Wahyuningsih; Netty Herawati (Universitas Darussalam Gontor, 2025)
Therapeutic communication is crucial in the process of healing people with mental illness after continuous confinement in stocks. In addition, mentally ill patients often endanger others and themselves, so pasung is used as a form of controlling their behavior so as not to endanger others. However, the practice of pasung for ODGJ is not a good solution so the pasung is removed and ODGJ requires continuous treatment. Therefore, this research aims to analyze, explore, and explore the phenomenon of therapeutic communication applied by the Selempang Mera Aba Idi Community in healing ODGJ after pasung. This research uses a descriptive qualitative method with a single case study approach. The research subjects are health workers and the patient's family. The object of research is therapeutic communication, challenges, support, and obstacles of the Selempang Mera Aba Idi Community in the healing process of ODGJ after being confined in stocks. Data collection techniques used observation, interviews, documentation, and audio-visual materials. The location of this research was Omben Sampang Madura. The results obtained from this study show that therapeutic communication between the Selempang Mera Aba Idi community and the family is very important in healing people with mental disorders after being confined in stocks, support in the form of biomedical therapy, and cognitive rehabilitation in the recovery process. There are barriers to drug compliance, uncooperative guardians of ODGJ, communication in language between health workers and families and ODGJ, and drug distribution.